Osteosarcopenia in Reproductive-Aged Women with Polycystic Ovary Syndrome: A Multicenter Case-Control Study - Kazemi, Maryam (J Clin Endocrinol Metab, 2020)
CONTEXT: Osteosarcopenia (loss of skeletal muscle and bone mass and/or function usually associated with aging) shares pathophysiological mechanisms with polycystic ovary syndrome (PCOS). However, the relationship between osteosarcopenia and PCOS remains unclear. OBJECTIVE: We evaluated skeletal muscle index% (SMI% = [appendicular muscle mass/weight (kg)] × 100) and bone mineral density (BMD) in PCOS (hyperandrogenism + oligoamenorrhea), and contrasted these musculoskeletal markers against 3 reproductive phenotypes (i): HA (hyperandrogenism + eumenorrhea) (ii); OA (normoandrogenic + oligoamenorrhea) and (iii), controls (normoandrogenic + eumenorrhea). Endocrine predictors of SMI% and BMD were evaluated across the groups. DESIGN, SETTING, AND PARTICIPANTS: Multicenter case-control study of 203 women (18-48 years old) in New York State. RESULTS: PCOS group exhibited reduced SMI% (mean [95% confidence interval (CI)]; 26.2% [25.1,27.3] vs 28.8% [27.7,29.8]), lower-extremity SMI% (57.6% [56.7,60.0] vs 62.5% [60.3,64.6]), and BMD (1.11 [1.08,1.14] vs 1.17 [1.14,1.20] g/cm(2)) compared to controls. PCOS group also had decreased upper (0.72 [0.70,0.74] vs 0.77 [0.75,0.79] g/cm(2)) and lower (1.13 [1.10,1.16] vs 1.19 [1.16,1.22] g/cm(2)) limb BMD compared to HA. Matsuda index was lower in PCOS vs controls and positively associated with SMI% in all groups (all Ps ≤ 0.05). Only controls showed associations between insulin-like growth factor (IGF) 1 and upper (r = 0.84) and lower (r = 0.72) limb BMD (all Ps < 0.01). Unlike in PCOS, IGF-binding protein 2 was associated with SMI% in controls (r = 0.45) and HA (r = 0.67), and with upper limb BMD (r = 0.98) in HA (all Ps < 0.05). CONCLUSIONS: Women with PCOS exhibit early signs of osteosarcopenia when compared to controls likely attributed to disrupted insulin function. Understanding the degree of musculoskeletal deterioration in PCOS is critical for implementing targeted interventions that prevent and delay osteosarcopenia in this clinical population.